How Organisations Know What They Know: A Survey of Knowledge Identification Methods among Australian Organisations - Newk-Fon Hey Tow, William; Venable, John; Dell, Peter (Deakin university, 2012)
Literature surrounding the Knowledge Management process of identifying what knowledge exists within an organisation is scarce. This research project set out to fill the research gaps surrounding that particular Knowledge Management process called Knowledge Identification. This paper reports on the findings of a survey sent to 973 Australian organisations to investigate their Knowledge Identification practices. The survey findings show that while organisations do perceive Knowledge Identification to be important, the practice of KI has not reached mainstream adoption yet. The reasons why and why not, and the range of methods organisations currently use to establish what knowledge exists within their four walls are identified. The survey findings also reveal two opposing approaches organisations take in practising KI: proactive KI and reactive KI.